Bite Force, Occlusal Contact and Pain in Orthodontic Patients during Fixed-Appliance Treatment - Nicoline Mie Therkildsen; Liselotte Sonnesen (Dentistry Journal, 2022)
Previously, bite force, occlusal contact and pain were investigated in orthodontic patients with moderate-to-severe malocclusion, but not in patients with minor malocclusion. The purpose of this study was to investigate changes in bite force, teeth in occlusal contact and pain in orthodontic patients with minor crowding before orthodontic treatment (T0), after bonding (T1), during treatment (T2), post-treatment (T3) and during retention (T4). In total, 27 patients (21 females, 6 males, median age 15.3 years) with neutral occlusion and normal craniofacial morphology were treated with non-extractions and fixed appliances. Differences in the registered data were analysed by a mixed linear model with repeated measures. Bite force and teeth in occlusal contact significantly decreased between T0 and T1 (p < 0.0001, respectively) and between T0 and T2 (p < 0.01, respectively). Bite force and teeth in occlusal contact significantly increased between T1 and T4 (p < 0.05, p < 0.0001, p < 0.001, respectively) and between T2 and T4 (p < 0.05, p < 0.0001, p < 0.01, respectively). No significant difference in pain was found. The results indicate that bite force and teeth in occlusal contact significantly decreased during treatment and reached baseline level at retention. The findings may prove valuable for informing orthodontic patients with minor malocclusion.